Study on Modification of Alkali-Free Liquid Accelerator of Mine-Used Wet-Mix Shotcrete - Chen Lianjun; Li Pengcheng; Pan Gang; Bian Wenhui (Advances in Materials Science and Engineering)
Compound properties of an alkali-free liquid accelerator are the mainstream of accelerator research and development in the present. Combined with the technical characteristics of wet-mix shotcrete in coal mines, organic high-polymer SWF is used to modify the accelerator because of improving the bond strength of the material and increasing the performance of antisagging. The mechanism of filling and thickening of SWF was analyzed from the aspects of pore characteristics and spatial structure of concrete. Through the determination of setting time, strength, and dispersibility, the optimum dose was determined, and a new style accelerator WIT-1 suitable for wet-mix shotcrete in coal mines was developed and applied on-site. The experimental results show that the addition of SWF increases the dispersibility of the accelerator product and the cohesiveness of concrete under the condition of ensuring strength and setting time, and the effect of modifying the accelerator to reduce the rebound of the wet-mix shotcrete is obvious.